Atividade analgésica, anti-inflamatóriae vasorelaxante de dois derivados pirazólicos: 5-[1-(4- fluorfenil)-1H-pirazol-4-IL]-2H-tetrazola(LQFM 020) e 5- [1-(2-fluorofenil)-1H-pirazol-4-IL]-2H-tetrazola (LQFM 039) - Oliveira, Lanussy Porfiro de (2014)
Inflammation is a complex process that aims to protect the body eliminating the harmful agent and to promote tissue repair is characterized by classic signs: pain, heat, redness and swelling as a result of failure to resolve the inflammatory process may occur loss of function. Control of pain and inflammation leads to the search for new drugs both analgesic and antiinflammatory drugs with good efficacy to aid in the treatment of these deseases. The aim of this study was to evaluate the pharmacological effects of two pyrazole derivatives. In acute nociception tests LQFM 020 (9, 17.5 and 35 mg/kg) and LQFM 039 (17.5, 35 and 70 mg/kg) reduced the number of writhing dose dependent manner to 53, 48 and 35; and 57, 52, 42, respectively, while the control group the number of writhes was 88. In the formalin test this antinociceptive effect was confirmed by the reduction in time reactivity to pain in both test phases, the time in the control group was 78 and 72s in the first phase and 150 and 128s in the second phase, with LQFM for 020 and 039 LQFM in the first phase was to reduce 50 and 47s and the second phase to 97 and 74s respectively. In bending the tail the groups of mice treated with LQFM 020 and LQFM 039 test were not able to increase the latency to thermal stimulus demonstrated that the analgesic effect does not involve central mechanisms. Furthermore, the results of the enzymatic activity of cyclooxygenase (COX) and phospholipase (PLA2) in vitro tests indicated no part of the mechanism of action involved in the activity of these compounds. In vascular reactivity tests LQFM 020 promoted vasorelaxant effect presenting maximum effect (Emax) of 93% in aortic preparations with endothelium and maximum effect (Emax) of 91% without endothelium . LQFM 039 also promoted vasorelaxant effect with maximum effect (Emax) of 80% when tested in preparations with endothelium and maximum effect (Emax) of 76% without endothelium, given this result, we investigated the mechanism of action of these compounds. Our results showed that LQFM 020 and LQFM 039 demonstrated the involvement of NO/cGMP pathway and suggest also the involvement of sensitive Ca2+ channels in the plasma membrane voltage.